Early Mobilisation of Patients with Acute Stroke: A survey of knowledge, attitude and practice health care professionals in South-west, Nigeria (2020)
BACKGROUND: Early mobilisation of acute stroke survivors has been associated with fewer deaths and better clinical outcomes. Yet, there are conflicting reports about the knowledge, attitude and practice of early mobilisation among clinicians. We investigated the knowledge, attitude and practice of early mobilization among health care professionals in South-West, Nigeria. MATERIALS AND METHODS: All the 159 health care professionals comprised 68(42.8%) nurses, 45(28.3%) physicians and 46(28.9%) physiotherapists involved in acute stroke care were surveyed using a content-validated questionnaire. Pearson’s Product Moment correlation and ANOVA were used to analyse data at p < 0.05. RESULTS: Most (n=147; 92.5%) of the participants agreed that early mobilization reduces complications of immobility. Majority of the HCPs were knowledgeable and had positive attitude towards early mobilisation (n=139; 87.4%). Attitude differed significantly across different healthcare professions (p=0.02). Most health care professionals (n=149; 93.7%) reported practicing early mobilization of acute stroke patients. There was a significant relationship between years of work experience and each of knowledge and attitude (p<0.05) CONCLUSIONS: Although, many health care professionals expressed concerns about the risks of early mobilization, including possibility of death, they reported practicing early mobilisation. It may be necessary to conduct a risk-benefit analysis of early mobilisation and provide appropriate practice guidelines to promote implementation. This could further enhance the health care professionals’ confidence in practicing early mobilisation and improve stroke care.